Micro-environment conditions, mycorrhizal symbiosis, and seed germination in Cypripedium candidum: strategies for conservation - Wake, Carol (Universidad de Costa Rica, 2015)
Cypripedium candidum Muhl. ex Willd. (White Lady’s Slipper), a terrestrial northern United States / southern Canada prairie orchid, reproduces both by seed and adventitious buds from older roots and rhi- zomes. To determine the pollination effects of diverse prairie micro-environments caused by com- peting foliage, particularly with respect to height and density of surrounding flora, ovary development (pollination success) versus ovary abortion (no pol- lination) was recorded for every flower in three diverse populations in eastern South Dakota, USA.